2015
DOI: 10.1371/journal.pone.0143556
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterisation and Diagnosis of Root-Knot Nematodes (Meloidogyne spp.) from Turfgrasses in North Carolina, USA

Abstract: Root-knot nematodes (Meloidogyne spp.) are the most common and destructive plant-parasitic nematode group worldwide and adversely influence both crop quality and yield. In this study, a total of 51 root-knot nematode populations from turfgrasses were tested, of which 44 were from North Carolina, 6 from South Carolina and 1 from Virginia. Molecular characterisation was performed on these samples by DNA sequencing on the ribosomal DNA 18S, ITS and 28S D2/D3. Species-specific primers were developed to identify tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 33 publications
4
46
0
4
Order By: Relevance
“…The low genetic diversity observed for M. javanica isolates during the present study was similar to results reported for other populations of M. javanica from different crops (Carneiro et al, 1998;Randig et al, 2002;Cofcewicz et al, 2004;Medina et al, 2017). This finding might be attributed to the parthenogenetic mode of reproduction in M. javanica, which results in clonal progenies (Triantaphyllou, 1985). Measured individuals of the selected five populations of M. javanica in the present study could not be sorted in regard of none of the diagnostic characters ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The low genetic diversity observed for M. javanica isolates during the present study was similar to results reported for other populations of M. javanica from different crops (Carneiro et al, 1998;Randig et al, 2002;Cofcewicz et al, 2004;Medina et al, 2017). This finding might be attributed to the parthenogenetic mode of reproduction in M. javanica, which results in clonal progenies (Triantaphyllou, 1985). Measured individuals of the selected five populations of M. javanica in the present study could not be sorted in regard of none of the diagnostic characters ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Also, we try to use Mantel test in linear shape for searching correlation between different matrix produced by RAPD and ISSR. Bootstrapping was done using the Winboot with 1000 replicates (Yap and Nelson, 1996) and measurements under 60 were excluded. Frequency analyses were performed to estimate the variance components and their significance levels of genetic variation within and among populations using GenALEx version 6.5 (Peakall and Smouse, 2006).…”
Section: Issr and Rapd Data Analysismentioning
confidence: 99%
“…These were used to inoculate 20 guava plants (a single egg mass per plant), which had been grown from seed in sterile medium for 3 months. At 45 days after inoculation, five plants were randomly chosen and several females were removed from the roots to confirm their molecular identification (Ye et al, 2015); all other plants were discarded. The selected plants were used as an inoculum source for the remaining experiments.…”
Section: Nematode Culturementioning
confidence: 99%
“…The PCR amplification using the designed primers was done as described by Ye et al (2015). The thermocycler conditions for amplification comprised initial denaturation at 94°C for 3 min, followed by 35 cycles of denaturation at 94°C for 30 sec, annealing for 45 sec at 55°C for ITS primers and 49°C for LSU primers, extension at 72°C for 1 min, and a final extension at 72°C for 10 min.…”
Section: Pcr Amplification Cleaning and Sequencingmentioning
confidence: 99%